A Comparison of the Associations between Alexithymia and both Non-suicidal Self-Injury and Risky Drinking: The roles of Cognitive-Emotional Variables and Biological Sex - Greene, Danyelle Jayne (Curtin University, 2021)
Danyelle explored whether difficulties in recognising and regulating emotions are related to self-injury and risky drinking, two behaviours commonly engaged in by students. She found that students who self-injure use this coping strategy to help regulate emotion, while those who drink in risky fashion may believe it gives them more confidence in communicating their emotions. She offers suggestions for how universities can use these results to reduce harm from self-injury and risky drinking on campuses.